Institutional framework for the Financial Supervision Authority's control over the activities of an insurance agent - Mariusz Bidziński; Bogusław Ulijasz (Journal of Modern Science, 2024)
Objectives The subject of consideration is the supervisory powers of the Financial Supervision Authority in terms of the control of insurance agents. Act of 15 Dec 2017 on Insurance Distribution introduced the possibility of conducting inspections of insurance agents' activities by supervisory authorities. The Financial Supervisory Authority is the body that supervises the financial market, including the supervision of activities related to the distribution and redistribution of insurance